Applications of mass spectrometry in identification of potential anticancer proteins from snake venoms - Othman, Iekhsan; Zainal Abidin, Syafiq Asnawi; Yusof, Fathin Athirah; Ismail, Ahmad Khaldun; Ahmad Rusmili, Muhamad Rusdi; Naidu, Rakesh (2018)
Mapping of the venoms proteins or now commonly called venomics have been the main approach towards understanding the venomous and destructive nature of venom proteins. These has led to high number of proteomics publications taking advantage of the LCMSMS technologies, that enable the accurate determinations of venoms constituents. The identification and purification of specific proteins such as L-amino acid oxidase and snake venom metalloproteinase (SVMP from crude venoms from Malaysian snakes such as the Malayan pit vipers (C. rhodostoma and C. purpureomaculatus) demonstrated selective cytotoxic activity on human colon cancer cells. Additionally, SVMP revealed strong inhibition of colon cancer cell migration as demonstrated from wound healing assay. HPLC subfractions with selective cytotoxic activity were analysed with LC-MS/MS and proteins that were detected with high confidence were purified such as L-amino acid oxidase (CR-LAAO) and snake venom C-type lectins (SNACLEC) rhodocetin and rhodocytin. LC-MS/MS and de novo sequencing of the isolated proteins from C. purpureomaculatus revealed amino acid variations highlighting a potential of a novel variant of each of the protein. CP-LAAO demonstrated strong cytotoxic activity and anti-proliferative activity, while CP-SVMP only affects the former. Caspase-3 induction activity was performed on CR-LAAO-, CP-LAAO- and CP-SVMP treated cells and revealed that stronger caspase-3 activity was detected from CR-LAAO and CP-LAAO at 24 hours of treatment and peaked at 48 hours. Bcl-2 cellular protein concentration assay was performed and significant drop of Bcl-2 concentration was identified from both CR- and CP-LAAO treated colon cancer cells. Morphological changes consistent with apoptosis on the LAAO treated cells further supported apoptosis induced cell death. Overall, these data provide evidence on the anticancer activity of several proteins from the venom of Malaysian pit vipers for therapeutic intervention of human colon cancer. We have also initiated anti-cancer studies on human brain cancer cells using venoms from Malaysian kraits, showed cytotoxic effects of B. candidus and B. fasciatus crude venoms and venom fractions in neuroblastoma cells. Preliminary data strongly suggested potent cytotoxic activities of the venom fractions on neuroblastoma cells. Overall, these data provided evidence on the application of LCMSMS in facilitating the potential anti-cancer activity from the venom of Malaysian snakes for therapeutic intervention.